Sustainable Development Perspectives of Solar Energy Technologies with Focus on Solar PhotovoltaicA Review - Izam N.S.M.N.; Itam Z.; Sing W.L.; Syamsir A. (MDPI, 2023)
Carbon dioxide; Climate change; Energy policy; Environmental protection; Fossil fuels; Gas emissions; Greenhouse gases; Planning; Solar concentrators; Solar energy; Solar power generation; Sustainable development; Energy sustainability; Green buildings; Greenhouse gas emissions; Renewable energies; Solar energy potential; Solar energy technologies; Solar industries; Solar photovoltaics; Sources of energy; Sustainable development; Energy efficiency